ANALISIS RASIO NON PERFORMING LOAN, NET INTEREST MARGIN DAN LOAN TO DEPOSIT RATIO TERHADAP RETURN ON ASSET PADA PERBANKAN UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ilyas Lamuda (LP2M Universitas Bina Mandiri Gorontalo, 2018)
The rapid development of the banking world and the high level of complexity can affect the performance of a bank. Weak internal conditions of the bank such as inadequate management, giving credit to groups or groups of their own business as well as capital that cannot cover the risks faced by the bank caused the bank's performance to decline. This study aims to analyze the effect of Non Performing Loans (NPL), Net Interest Margin (NIM) and Loan to Deposit Ratio (LDR) on Return on Assets (ROA) in general banking listed on the Indonesian Stock Exchange. Data collection method through documentation, i.e data collection techniques are carried out by studying documents, financial statements obtained from general banking listed on the Indonesian stock exchange, sample selection using purposive sampling method as many as 20 banks as samples from 45 banks registered in 2016 - 2017. Data were analyzed using Multiple Linear Regression Analysis. Data processing using SPSS (Statistical Package for Social Science) software. From the results of the test F calculated at 1,300 with (Prob> F) value of 0.029. This means that the value of P-value or significance is less than 0.05 which indicates that the variable Non Performing Loans (NPL), Net Interest Margin (NIM), and Loan to Deposit Ratio (LDR) together have a significant influence on Return On Assets (ROA). Based on the results of the t-test concluded that Non-Performing Loans (NPL), and Net Interest Margin (NIM) have a positive effect on Return on Assets (ROA)